2004
DOI: 10.5858/2004-128-991-fntr
|View full text |Cite
|
Sign up to set email alerts
|

Febrile Nonhemolytic Transfusion Reactions

Abstract: Context.—Febrile nonhemolytic transfusion reactions (FNHTRs) cause unwelcome interruptions during the course of blood product transfusions and necessitate measures to verify the nature of the reaction and to exclude certain dangerous reactions, such as hemolytic and septic phenomena. Objective.—To examine transfusion medicine data to determine the clinical implications of the routine administration of antipyretic medication to adult patients before transfusion for the prevention of FNHTRs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, this was a small trial, and only 21 patients (7 in the active drug group, and 14 in the placebo group) experienced febrile events 147 . The other study supporting the PICO question was a single‐center retrospective case series with no control group (LOE 6, poor) 148 …”
Section: Domain 1: Prevention Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this was a small trial, and only 21 patients (7 in the active drug group, and 14 in the placebo group) experienced febrile events 147 . The other study supporting the PICO question was a single‐center retrospective case series with no control group (LOE 6, poor) 148 …”
Section: Domain 1: Prevention Strategiesmentioning
confidence: 99%
“…147 The other study supporting the PICO question was a single-center retrospective case series with no control group (LOE 6, poor). 148 Two randomized placebo controlled trials oppose the PICO question (LOE 6, good), although are confounded by the concurrent use of an antihistamine with an antipyretic in the premedication arms. 149,150 A single-center study included 55 hematology/oncology patients, that received 98 leukoreduced, irradiated, single-donor apheresis platelet transfusions.…”
Section: Agreement: 13/13 Evidence Summarymentioning
confidence: 99%
“…A previous study reported a FNHTR rate of 0.09% in 80.0% of patients who received transfusions after routine antipyretic premedication; however, premedication did not prevent other more severe TRs. 16 A Cochrane review of three randomized controlled trials reported no evidence to support the administration of premedication to minimize the risk of non-haemolytic transfusion reactions. 17 The British Committee for Standards in Haematology Blood Transfusion Task Force recommends antipyretic premedication for patients with recurrent FNHTR, no antihistamines or steroid premedication for mild recurrent allergic reactions, and consideration of antihistamine prophylaxis for recurrent moderate or severe allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggesting a reduced incidence of febrile reactions in patients premedicated with paracetamol [34][35][36][37] are counterbalanced by studies with negative results. [38][39][40][41][42] Studies on patients with a previous febrile reaction showed no difference in reaction rates compared to those with no previous reaction.…”
Section: Febrile Non-haemolytic Transfusion Reactionsmentioning
confidence: 99%
“…Reports on prevention of FNHTRs using premedication with paracetamol (acetaminophen), usually in a dose of 500–650 mg, are of inadequate quality, include both primary and secondary prevention, and report contradictory results. Studies suggesting a reduced incidence of febrile reactions in patients premedicated with paracetamol 34–37 are counterbalanced by studies with negative results 38–42 . Studies on patients with a previous febrile reaction showed no difference in reaction rates compared to those with no previous reaction 39,40 .…”
Section: Management Of Patients With Repeated Reactionsmentioning
confidence: 99%